Analysis of the Prevalence of Socially Significant Non-communicable Diseases in the Russian Federation at the Present Stage - Yu. Stasevich, Natalia; S.I. , Kozlov; A.V. , Viryasov (International Journal of Psychosocial Rehabilitation, 2020)
Socially significant diseases represent enormous damage to society associated with high morbidity, temporary disability, disability, and mortality. An integrated approach to the treatment of patients with this group of diseases requires huge costs for diagnosis, rehabilitation, prevention of premature mortality, and social support for patients, as well as preventive measures against crime (drug and alcohol abuse). The aim of the study was to analyze the epidemiological situation on the prevalence of socially significant noncommunicable diseases. The methods of analytical processing of official statistics (www.Gsk.ru) were used in the present study. It is established that the priority solution to the problem of social diseases is the prevention of risk factors of their development with the implementation of modern technologies of prevention. This will allow for purposeful and successful use of economic and medical resources for primary prevention of socially significant diseases and improvement of the population.